PRELIMINARY STUDY OF KUNTOWIJOYO STUDENT VALUE ASSESSMENT INSTRUMENTS (HIGH SCHOOL CASE STUDY) - Azam Hanif Adin (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The purpose of education is to develop the potential that exists in humans. Making humans as human beings. Educating forms humans to have real character. Many studies on the application of character education begin when a human is in the bench of study. Not only about science, but also about the science of life. So it takes a character to make humans better. Kuntowijoyo in his social theory explains that human character should be brought to the values of humanization, liberation, and transcendence. Where the three of them are related and support each other to present a better human figure. The planting of prophetic values proclaimed by Kuntowijoyo will truly be felt by the community where during their education they are able to continue to be evaluated. So that a student is able to continue to develop and get character development. Therefore we need an initial study to see whether the development of an instrument to measure the prophetic value of Kuntowijoyo in students is needed or not. In order to see this, a study was conducted to see the need for assessment in several senior high schools in Central Java Province. There are 6 SMA schools representing 6 different districts or cities in Central Java. Data obtained by using simple interviews to 6 respondents who represent the 6 existing SMA. School selection was carried out by looking at the majority population in Central Java who were Muslim, therefore 6 Islamic-style high schools were taken with a populist reputation regarding the cultivation of good character values. Based on the data obtained, it is necessary to have an instrument that can be used and standardized to support character education. The instrument that will show the evaluation value of character education is seen from the prophetic value of Kuntowijoyo. An instrument that can be used by various types of educational institutions in Indonesia